Dechema chemistry data series : vapor liquid equilibrium data collection 2c Organic hydroxy compounds, alcohols (supplement 1) - Gmehling, J.; Onken, U.; Arlt, W. (Frankfurt Dechema, 1982)
part 2c
Keywords: Vapor-Liquid equilibrium; Binary mixtures -- Data tables and diagrams